2004
DOI: 10.1291/hypres.27.433
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of Endothelin-1 (1-31): Induction of Mesangial Cell Migration and Facilitation of Monocyte Recruitment through Monocyte Chemoattractant Protein-1 Production by Mesangial Cells

Abstract: We previously found that human chymase selectively cleaves big endothelin-1 (ET-1) at the Tyr

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 43 publications
2
23
0
1
Order By: Relevance
“…Finally, some groups have suggested that ET-1 (1-31) acts as a selective ET A agonist, albeit in in vitro models (Ishizawa et al, 2004;Zhou et al, 2006). In vivo, in the mouse model, however, ET A or ET B receptor blockade reduce or amplify, respectively, the pressor responses to Big ET-1, ET-1 (1-31), and ET-1.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some groups have suggested that ET-1 (1-31) acts as a selective ET A agonist, albeit in in vitro models (Ishizawa et al, 2004;Zhou et al, 2006). In vivo, in the mouse model, however, ET A or ET B receptor blockade reduce or amplify, respectively, the pressor responses to Big ET-1, ET-1 (1-31), and ET-1.…”
Section: Discussionmentioning
confidence: 99%
“…RMCs were isolated from intact glomeruli of 4-to 6-week-old male Sprague-Dawley rats and maintained in 18% fetal bovine serum (FBS) and RPMI 1640 as described previously (Ishizawa et al 2004). For the experiments, cells from passages 5 to 9 were used after 24-48 h of serum depletion.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…To assess cell migration, a modified Boyden chamber assay was performed with minor modification to the method described previously (Ishizawa et al 2004). The assay was performed using Transwell chambers (6 .…”
Section: Rmc Migration Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess cell migration, especially invasive displacement, a modified Boyden chamber assay was performed by minor modification to the method described previously (31). The assay was performed using Transwell chambers (6.5 mm, model 3422; Costar, Cambridge, USA) with an 8-ÎŒm pore polycarbonate membrane.…”
Section: Modified Boyden Chamber Assaymentioning
confidence: 99%